(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper presents an efficient Face Recognition Using Eigen Face approach and a novel scheme of protecting the hidden transmission of face biometrics using authentication Watermarking technique. Face is a complex multidimensional visual model and developing a computational model for face recognition is difficult. The paper presents a methodology for face recognition based on information theory approach of coding and decoding the face image. Proposed methodology is a connection of two stages – feature extraction using principle component analysis and recognition using the feed forward back propagation Neural Network. The proposed scheme uses watermark embedding algorithm. Compared with personal identification number codes, method in diverse application but their validity must be guaranteed. Watermarking technique provides solution to ensure the validity of biometrics; proposed scheme is composed of three parts: watermark embedding, data embedding and data extraction. One of the applications of our proposed scheme is verifying data integrity for images transferred over the internet